2009
DOI: 10.1111/j.1538-7836.2009.03544.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with deep vein thrombosis: the F11 locus

Abstract: To cite this article: Li Y, Bezemer ID, Rowland CM, Tong CH, Arellano AR, Catanese JJ, Devlin JJ, Reitsma PH, Bare LA, Rosendaal FR. Genetic variants associated with deep vein thrombosis: the F11 locus. J Thromb Haemost 2009; 7: 1802-8. Summary. Background: Recent studies have found associations between deep vein thrombosis (DVT) and single nucleotide polymorphisms (SNPs) in a 4q35.2 locus that contains genes encoding factor XI (F11), a cytochrome P450 family member (CYP4V2), and prekallikrein (KLKB1). Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 19 publications
8
117
2
1
Order By: Relevance
“…The association of F11 SNPs with VT risk is not new because 2 F11 SNPs, rs2036914 and rs2289252, were previously found to be associated with VT in the Leiden Thrombophilia study. 19 None of these 2 SNPs was available in our GWAS dataset, nor were they in strong linkage disequilibrium with any of the F11 SNPs associated with VT in the present work (supplemental Table 5). In-depth haplotype analysis would be further required to disentangle the exact contribution of F11 SNPs to VT risk and aPTT variability, but this research is out of the scope of the present report.…”
Section: Resultsmentioning
confidence: 79%
“…The association of F11 SNPs with VT risk is not new because 2 F11 SNPs, rs2036914 and rs2289252, were previously found to be associated with VT in the Leiden Thrombophilia study. 19 None of these 2 SNPs was available in our GWAS dataset, nor were they in strong linkage disequilibrium with any of the F11 SNPs associated with VT in the present work (supplemental Table 5). In-depth haplotype analysis would be further required to disentangle the exact contribution of F11 SNPs to VT risk and aPTT variability, but this research is out of the scope of the present report.…”
Section: Resultsmentioning
confidence: 79%
“…Nine SNPs were added from a large SNP association analysis, including subsequent fine mapping that we performed recently in LETS and MEGA. 15,16 Another added SNP was recently identified in a follow-up study of a genome-wide association study and replicated in the FARIVE study and the MEGA study. 17 Among the 40 SNPs in the initial selection, we studied linkage disequilibrium and mutually adjusted SNPs within genes.…”
Section: Snp Selectionmentioning
confidence: 90%
“…Table 1 lists all associations between SNPs and venous thrombosis in the MEGA population and the average estimated effect size in the literature. [13][14][15][16][17][19][20][21][22][23][24][25][26] Not all SNPs were associated with venous thrombosis in our study populations; nevertheless, we included all 31 SNPs in the genetic risk score because these SNPs had been associated with venous thrombosis in other studies.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Three SNPs were strongly associated with VT: rs13146272 in CYP4V2, rs2227589 in SERPINC1 and rs1613662 in GP6; 4 additional SNPs (in CYP4V2, KLKB1, and F11) were also associated with VT. The effect of CYP4V2 and GP6 loci polymorphisms (SNPs rs1613662 and rs13146272) was further confirmed by Tregouet et al (2009), and the effect of F11 polymorphisms (SNPs rs2289252 and rs2036914) by Li et al (2009). Recently, in a multi-stage multi-design study, Antoni et al (2010) found evidence that BAI3 locus (encoding brain specific angiogenesis inhibitor 3) is associated with early-onset VTE; rs9363864-AA genotype was associated with a lower risk for VTE and low levels of FVIII and VWF.…”
Section: New Approaches and Research Strategies In Inherited Thrombopmentioning
confidence: 84%